Diagnosis of Left Ventricular Diastolic Dysfunction Using Cardiac Magnetic Resonance Imaging: Comparison of Volume-Time Curves Derived from Long- and Short-Axis Cine Steady-State Free Precession Datasets - Schaafs, Lars-Arne; Wyschkon, Sebastian; Elgeti, Matthias; Nagel, Sebastian Niko; Knebel, Fabian; Steffen, Ingo G.; Makowski, Marcus R.; Hamm, Bernd; Elgeti, Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To evaluate the diagnostic performance of diastolic function parameters derived from long-axis (LAX) planimetry compared with short-axis (SAX) volumetry in cardiac magnetic resonance imaging.Materials and Methods Cine steady-state free precession (SSFP) datasets of 15 healthy participants (8 young and 7 middle aged) and 25 patients with echocardiographically proven diastolic dysfunction (9 mild, 9 moderate, and 7 severe) were retrospectively included. Volume-time curves for assessing left ventricular (LV) function were obtained by manually contouring the LV endocardial borders in SAX and LAX datasets. The time needed for contouring was recorded for each dataset. The following LV parameters were determined: end-diastolic volume (EDV), end-systolic volume (ESV), ejection fraction (EF), myocardial mass (MM), time to peak filling rate (TPFR), normalized peak filling rate (nPFR), and the ratio of early to late peak filling rate (E/A ratio). A Wilcoxon signed-rank test was used to compare subgroups based on age and severity of diastolic dysfunction for statistical differences. Intraclass correlation coefficients were used to assess intermethod and interobserver reliability.Results Accuracy for the diagnosis of diastolic dysfunction was highest for E/A (mild diastolic dysfunction) and nPFR (any stage of diastolic dysfunction) derived from LAX datasets (E/A: area under the curve (AUC) = 0.97, sensitivity of 68 % and specificity of 100 %; nPFR: AUC = 0.84, sensitivity of 84 % and specificity of 80 %). Diastolic parameters showed a moderate to good intraclass correlation between both methods. The mean differences in EDV, ESV, EF, and MM were 5.3 ml, 1.9 ml, 3.5 %, and 11 g, respectively (each p < 0.001). Significantly less time was needed to derive volume-time curves from LAX images (median 14:45 min, interquartile range 14:15–15:53 min versus median 29:25 min, interquartile range 28:12–32:22 min; p = 0.001). The interobserver reliability was generally good to excellent.Conclusion Diastolic function parameters derived from left ventricular LAX planimetry have high diagnostic performance and can be obtained in significantly less time compared with SAX volumetry. These findings may pave the way for routine use of LAX planimetry in the clinical diagnosis of diastolic dysfunction.Key points: Citation Format
Keywords: cardiac function; magnetic resonance imaging; diastolic dysfunction; long axis; short axis